Cumulative downstream turbine‐induced mortality and thresholds for facilitating upstream passage of American eel. (1st December 2021) - Haxton, Tim
Abstract: American eels ( Anguilla rostrata ) are vulnerable to turbine‐induced mortality during outmigration along regulated rivers. Turbine‐induced mortality is cumulative when multiple facilities are encountered along the route. This level of mortality may be unsustainable such that facilitating upstream movement ostensibly for recovery purposes, may in fact be detrimental to the population or an ecological trap. The objectives of this study were to estimate a theoretical threshold for facilitating upstream movement passed hydroelectric facilities and estimating cumulative turbine mortality within waterbodies across American eel's historical range within Ontario, Canada. A stage‐structured model was used to estimate mortality thresholds parameterized by published life stage survival probabilities using a maternal effect and altering silver eel survival to mimic turbine mortality. The threshold was exceeded when population growth (λ) declined below 1.0. Site mortality was estimated based on the generating station characteristics including turbine type, size, proportion of flow through turbines, and sluice gate height. Cumulative mortality within a waterbody was projected using a Bayesian network (i.e., conditional probability) and the calculated site‐specific mortality. The survival required for a stable population using the stage‐structured model was 0.75; (0.65–0.85) therefore, annual mortality greater than 0.25 (0.15–0.35) would result in population decline (λ < 1). The effects of turbine mortality increased with additional hydroelectric facilities encountered along the route. Across Ontario, there was no eel habitat deemed to be safe in terms of levels of cumulative turbine mortality during outmigration. Moreover, 89.1% of eel habitat was considered to be within the cautionary range of turbine mortality, whereas 10.9% of eel habitat was considered to be above the threshold for sustainable passage during outmigration. Lake Ontario accounted for 98.2% of the area within the cautionary range, whereas most of the tributaries and watersheds associated with the Ottawa River and Lake Ontario were above the threshold.